2017
DOI: 10.1182/bloodadvances.2017010819
|View full text |Cite
|
Sign up to set email alerts
|

Redefining the role of etoposide in first-line treatment of peripheral T-cell lymphoma

Abstract: Key Points Etoposide addition/chemo-intensification has little role in first-line treatment of PTCL in Asian populations, regardless of subtype or age. Upfront hematopoietic stem-cell transplantation as consolidation seems like a legitimate choice in patients with PTCL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…There were two,18,19 three,19,21,22 three,18,19,21 three,18,21,22 and two18,21 included studies that reported complications of neutropenia, anemia, thrombocytopenia, leukopenia, and vomiting, respectively. However, the results showed no significant heterogeneity for these five indicators, respectively (I 2 <50% and P >0.05); therefore, the fixed-effect model was applied.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were two,18,19 three,19,21,22 three,18,19,21 three,18,21,22 and two18,21 included studies that reported complications of neutropenia, anemia, thrombocytopenia, leukopenia, and vomiting, respectively. However, the results showed no significant heterogeneity for these five indicators, respectively (I 2 <50% and P >0.05); therefore, the fixed-effect model was applied.…”
Section: Resultsmentioning
confidence: 99%
“…According to the Egger’s test, we found no publication bias in aspects of all outcomes ( P >0.05; Table 2). Additionally, we also assessed the influence of each individual study on the combined effect size by sensitivity analysis, and the result of thrombocytopenia was inversed after removing Kim’s article19 (RR =1.11, 95% CI: 0.71–1.73, P =0.654). We did not perform sensitivity analysis for neutropenia and vomiting, since there were only two eligible studies.…”
Section: Resultsmentioning
confidence: 99%
“…Since literature data and bio-informatic analysis suggest the functional involvement of ENPP2 in Epstein-Barr viral infection [26], and we found it to be up-regulated both in vitro and in vivo , we hypothesized that there was a link between HBV replication and the ENPP2 protein. Accordingly, one control siRNA and two ENPP2-specific siRNA sequences were used to transfect the HepG2.2.15 virus-producing cell line.…”
Section: Resultsmentioning
confidence: 99%
“…However, as it was demonstrated by a German group [5], benefit of etoposide was limited in only younger patients with normal LDH, so it would be less likely applicable to our patient population. In addition, recent evidence showed that adding etoposide to CHOP had little benefit for PTCL in Asian populations [21].…”
Section: Discussionmentioning
confidence: 99%